Continuing Education Outcomes for Advance Care Planning: A Systematic Review of the Literature. Issue 1 (8th January 2021) - Pearse, Wendy; Saxon, Robyn; Plowman, Greg; Hyde, Mervyn; Oprescu, Florin
Abstract : Introduction: Advance care planning (ACP) is a process of considering future health and care needs for a time when a person may be unable to speak for themselves. Health professional continuing education programs have been proposed for facilitating patient participation in ACP; however, their impacts on participants, patient and clinical outcomes, and organizational approaches to ACP are not well understood. Methods: This systematic literature review examined interventional studies of education programs conducted with health professionals and care staff across a broad range of settings. Five electronic databases were searched up to June 2020, and a manual search of reference lists was conducted. The quality of studies was appraised by the first, second, and third authors. Results: Of the 7993 articles identified, 45 articles met the inclusion criteria. Program participants were predominantly medical, nursing, and social work staff, and students. Interventions were reported to improve participants' self-perceived confidence, knowledge, and skills; however, objectively measured improvements were limited. Multimodal programs that combined initial didactic teaching and role-play simulation tasks with additional activities were most effective in producing increased ACP activity in medical records. Evidence for improved clinical outcomes was limited. Discussion: Further studies that use rigorous methodological approaches would provide further evidence about what produces improved patient and clinical outcomes. Needs analyses and quality indicators could be considered to determine the most appropriate and effective education resources and monitor their impacts. The potential contribution of a broader range of health professionals and interprofessional learning approaches could be considered to ultimately improve patient care.